Gender differences in problem discussion : the depressive effect of co-rumination in same-sex friendships - Taylor, L; Laura Taylor (2014)
The main objective of this thesis was to examine gender differences in co-rumination using observational, experimental, and diary methods. At the start of this project there were no existing studies which had assessed co-rumination in this way and this thesis intended to be an exploratory investigation of co-rumination using these methods. Rose (2002) defined co-rumination as ‘excessively discussing problems within a dyadic relationship’ (p. 1830) and used it to explain why females have closer, more supportive, friendships (Rose & Rudolph, 2006) but are also more susceptible to depression (Weissman & Klerman, 1977). Her findings suggest that co-rumination has maladaptive outcomes for females (increased depression and anxiety) but not for males. The six studies within this thesis aimed to investigate the outcomes of co-rumination using adult (Studies 1- 4), adolescent (Studies 5 and 6) and child samples (Study 6). The first three studies within this thesis assessed co-rumination using dyadic analyses of observational and experimental data. The results of these studies indicated that scores from the co-rumination questionnaire (CRQ) and the co-rumination coding scheme (CRCS) were associated with affect, but that the co-rumination manipulation used in Study 3 had no effect on levels of affect. CRCS was mainly predictive of depressive outcomes whereas CRQ was predictive of both depressive and anxious outcomes. The research indicated that CRQ scores positively correlated across the two dyad members. However, each dyad member’s score showed different associations with affect, depending on whether the dyad member was presenting his or her own problem for discussion. The diary studies indicated that co-rumination was best assessed using daily items which were more predictive of changes in positive and negative affect than the CRQ. It was clear from the studies within this thesis that co-rumination did not only have negative outcomes for females, and that future research should examine the outcomes of co-ruminative discussions for males and females. It was suggested that future researchers should conduct similar experimental research to Study 3 but that they should include multiple co-ruminative interactions and more immediate assessments of co-rumination in the days following a co-ruminative interaction.